Enhanced performance of next-generation sequencing diagnostics compared with standard of care microbiological diagnostics in patients suffering from septic shock - Grumaz, Silke; Decker, Sebastian; Weigand, Markus A.; Brenner, Thorsten (Critical care medicine, 2019)
Objectives: Culture-based diagnostics represent the standard of care in septic patients, but are highly insensitive and in many cases unspecific. We recently demonstrated the general feasibility of next-generation sequencing-based diagnostics using free circulating nucleic acids (cell-free DNA) in plasma samples of septic patients. Within the presented investigation, higher performance of next-generation sequencing-based diagnostics was validated by comparison to matched blood cultures. - Design: A secondary analysis of a prospective, observational, single-center study. - Setting: Surgical ICU of a university hospital and research laboratory. - Patients: Fifty patients with septic shock, 20 uninfected patients with elective surgery as control cohort. - Interventions: None. - Measurements and Main Results: From 256 plasma samples of 48 septic patients at up to seven consecutive time points within the 28-day observation period, cell-free DNA was isolated and analyzed by next-generation sequencing and relevance scoring. In parallel, results from culture-based diagnostics (e.g., blood culture) were obtained. Plausibility of blood culture and next-generation sequencing results as well as adequacy of antibiotic therapy was evaluated by an independent expert panel. In contrast to blood culture with a positivity rate of 33% at sepsis onset, the positivity rate for next-generation sequencing-based pathogen identification was 72%. Over the whole study period, blood culture positivity was 11%, and next-generation sequencing positivity was 71%. Ninety-six percent of positive next-generation sequencing results for acute sepsis time points were plausible and would have led to a change to a more adequate therapy in 53% of cases as assessed by the expert evaluation. - Conclusions: Our results show that next-generation sequencing-based analyses of bloodstream infections provide a valuable diagnostic platform for the identification of clinically relevant pathogens with higher sensitivity and specificity than blood culture, indicating that patients might benefit from a more appropriate therapy based on next-generation sequencing-based diagnosis.